2012
DOI: 10.2308/jiar-50353
|View full text |Cite
|
Sign up to set email alerts
|

Management Motive, Weak Governance, Earnings Management, and Fraudulent Financial Reporting: Malaysian Evidence

Abstract: This study examines ten factors associated with fraudulent financial reporting (FFR) in Malaysian publicly listed companies. We hypothesize that three factors proxy for management rationalization, four factors proxy for management motives, and three factors proxy for the opportunity to commit fraud. Our sample consists of 53 fraud firms convicted of securities fraud and 53 no-fraud firms, all of which were listed on the Bursa Malaysia and have a complete set of data from 1996–2007. With regard to rationalizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
113
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(125 citation statements)
references
References 54 publications
9
113
0
3
Order By: Relevance
“…It has been found that EM is significantly and positively related to the occurrences of fraudulent financial reporting (Hasnan et al, 2013). This is in line with the argument of Perols & Lougee (2011), who documented a positive relationship between prior year EM and fraud in US firms.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…It has been found that EM is significantly and positively related to the occurrences of fraudulent financial reporting (Hasnan et al, 2013). This is in line with the argument of Perols & Lougee (2011), who documented a positive relationship between prior year EM and fraud in US firms.…”
Section: Introductionsupporting
confidence: 82%
“…The alleged fraudulent listed firms in Malaysia have aggressively used EM prior to the alleged fraud year (Hasnan, Abdul-Rahman, & Mahenthiran, 2013;Sulaiman, Danbatta, & Rahman, 2014) and continue to smoothen their earnings in the years subsequent to the alleged fraud year (Sulaiman et al, 2014). It has been found that EM is significantly and positively related to the occurrences of fraudulent financial reporting (Hasnan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In the positive view of RPTs, RPTs are perceived as value-enhancing mechanisms that are designed to improve efficiency in an organization. RPTs as value-enhancing mechanisms have been discussed from the perspective of efficient transaction [2], contracting efficiency [3], bonding mechanisms [4] and institutional needs [5]. In the negative view of RPTs, RPTs are perceived as a form of private benefits of control, which is used as a mean of transferring firms" wealth to the controlling shareholders (or management) at the expense of other stakeholders.…”
Section: The Economic Consequences Of Rptsmentioning
confidence: 99%
“…The higher frequency of related party transactions for fraud firms suggests that the presence of related party transactions may reflect heightened fraud risk. For Asian In the context of Malaysia, [5] highlights the case of Transmile Bhd for which two Independent Non-executive Directors were sentenced a one-year prison term. In that case, sales and real estate transactions between insider directors and executives were abused, resulting in detrimental effect to the minority shareholders.…”
Section: Accounting Irregularities In Rptsmentioning
confidence: 99%
See 1 more Smart Citation